IMPLEMENTASI SISTEM PENGELOLAAN ARSIP KORESPONDENSI BERBASIS LAMAN PORTAL (KASUS: KAPANEWON MLATI, SLEMAN, YOGYAKARTA) - Jeffry Andhika Putra; Asti Ratnasari (Universitas Alma Ata, 2023)
The development of technology is presently getting information as an important pillar with the functional exertion of an institution to achieve pretensions that are salutary to the institution. One technology presently truly useful and constantly used is the World Wide Web known as the website. Indeed, now the web has entered every agency, including government agencies.This study aimed to design a correspondence library operation system at Kapanéwon Mlati for library government letter data (data on incoming letters, gregarious letters, incoming appointments, and gregarious appointments). With the design of this system, it's hoped that it can be executed into storage and library operation systems in agreement with their separate fields in the system.Data from this study indicates that the operation of the Kapanéwon Mlati libraries has not been carried out optimally. This can be seen from the use of program books that are not accompanied by disposition wastes, library storage systems that are still combined, controls that do not use form cards, and the actuality of damaged and dirty libraries, with this application, is hoped that can achieve efficiency and effectiveness in managing mail archives by implementing a mail archive management information system to provide ease of archiving mail archive data in Kapanéwon Mlati.